Common Fixed Point Theorem for Four Weakly Compatible Self Maps on a Complete S-Metric Space - Srinivas, A. (Communications in Mathematics and Applications, 2022)
In the present paper, we establish a common fixed point theorem for four weakly compatible self maps of a S-metric space.